Helicobacter pylori Secondary Antibiotic Resistance after One or More Eradication Failure: A Genotypic Stool Analysis Study - Giuseppe Losurdo; Martino Mezzapesa; Ilaria Ditonno; Mariapaola Piazzolla; Maria Pricci; Bruna Girardi; Francesca Celiberto; Grazia Galeano; Giuseppe Riezzo; Francesco Russo; Andrea Iannone; Enzo Ierardi; et al. (Antibiotics, 2024)
Helicobacter pylori (H. pylori) antibiotic resistance is the leading cause for unsuccessful eradication therapy. After one or more failures, the chance of encountering secondary antibiotic resistance increases. The aim of this study was to characterize genotypic secondary resistance in a cohort of southern Italian H. pylori patients with at least one previous failure. Such patients collected stool samples using a dedicated kit (THD fecal testTM), and bacterial DNA was extracted and amplified using RT-PCR. Resistance to clarithromycin, amoxicillin, metronidazole, levofloxacin, and tetracycline was assessed using a high-resolution melting curve. We enrolled 50 patients. A total of 72% of patients failed one previous antibiotic course, 16% failed two, 10% failed three, and 2% failed four. The rate of secondary antibiotic resistance was 16% for clarithromycin, 18% for metronidazole, 14% for amoxicillin, 14% for levofloxacin, and 2% for tetracycline. Among the eight clarithromycin-resistant patients, five (62.5%) previously received a clarithromycin-based regimen. The same rate was 33.3% (3/9) for metronidazole. The only tetracycline-resistant patient had received Pylera. In conclusion, our data seem to show that, even though secondary resistance is not very high, resistance to clarithromycin could be very likely related to previous exposure to this antibiotic.